Investigation of some trace elements in Raipur Industrial area and its surrounding, Raipur District. - Sahu, Bed lal; Pardhi, Om Prakash; Upadhyay, Manish; Dwivedi, Pratima Rani; Augur, M R; Pandey, Rajiv Ratna; Pathak, Krishna Kumar (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The paper deals with determination of eight trace metals namely. Copper, Iron, Mangnese, Zinc, Nickel, Chromium Lead and Mercury in the ground water of different sites of Raipur Industrial area of Raipur district . All activities carried out on the ground surface have direct or indirect impact on the ground water whether associated with urban ,industrial or agricultural activities large scale concentrated source of pollutants, such as industrial discharges and sub surface injection of chemicals and hazardous are obvious source of ground water pollutants. This study was carryout in the month of during summer 2013. The samples were collected from seven different source of Raipur Industrial area of Raipur. The results obtained are compared with safe limits in ppm for heavy metals laid down by BIS, WHO, ICMR, APHA. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>